PROGRESS TOWARDS INCLUSIVE PRIMARY EDUCATION IN SELECTED WEST AFRICAN COUNTRIES (African Disability Rights Yearbook, 2021)
Using Nigeria, Ghana and Sierra Leone as the main case study, this commentary discusses developments on inclusive education in the West African Region. It evaluates the extent to which domestic legislation and policy framework in the three West African countries complies with the normative standards set in article 24 of Convention on Rights of Persons with Disabilities (CRPD) the commentary observes that none of the legislative and policy frameworks in the three West African States completely meets the standards set in article 24 of the CRPD or the newly adopted Protocol to the African Charter on Human Peoples’ Rights on the Rights of Persons with Disabilities.